Bird‐repellent effects on bait efficacy for control of invasive mammal pests. Issue 8 (25th September 2014) - Cowan, Phil; Brown, Sam; Forrester, Guy; Booth, Lynn; Crowell, Michelle
Abstract BACKGROUND Repellents to reduce crop damage from birds and mammals have been investigated extensively, but their efficacy in reducing risk to non‐target birds in aerial poisoning operations for control of mammal pests is less known. We assessed the impact on bait acceptability, palatability and kill efficacy for captive wild rats (Rattus rattus L.) and possums (Trichosurus vulpecula Kerr) of adding bird repellents (anthraquinone and d‐pulegone) to baits used for their control in food choice trials. RESULTS For possums, anthraquinone at 0.25% reduced acceptability and palatability but not the efficacy of poison baits, whereas d‐pulegone at 0.17% had no significant effects. Rats showed little response to d‐pulegone, but developed a marked aversion to prefeed baits containing anthraquinone at both 0.1 and 0.25%, such that almost no exposed rats ate poison baits and mortality was reduced significantly. The aversion induced by anthraquinone was generalised to the bait, as anthraquinone‐exposed rats did not eat bait with only d‐pulegone. CONCLUSION Anthraquinone is not suitable for inclusion in bait for rat control at the concentrations tested, and also presents some risk to efficacy for possum control. D‐pulegone would be suitable for inclusion in bait for possums and rats, but problems related to its volatility in bait manufacture and storage would need to be overcome. Further studies should focus on an alternative secondary repellent, or on establishing the maximum anthraquinone concentration that does not reduce efficacy for rats and testing whether or not that concentration is sufficient to repel native birds from baits reliably. © 2014 Society of Chemical Industry